Challenges in developing Clan jetties as heritage attractions for conservation and tourism in Penang Malaysia - Chan , Ngai Weng (Environmental Management Society, Malaysia, 2011)
Penang Island has a rich historical background being the first site to be colonised by the British in 1786. Consequently, the island also has many old settlements that are now marketed as heritage attractions. Clan jetties are unique and have attractive architecture, many being designated as heritage sites. They also double up as a new attraction to tourists. Development and political preeures pose the greatest dangers to their survival, as is poor environmental management, poverty and out-migration and expose to environmental hazards. THis paper identifies the potentials of clan jetties as heritage building and tourism attractions. It reports on surveys of clan jetties in Penang and highlights the extent to which tourists are aware of such jetties and make attempts to visit them.Finally, it provides suggestions as to how best to develop the clan jetties in a sustainable way.